(3MGTjI EdgjGJ GdJLQjOs - (3eLghds ((3UGdM Hf NdjaI OGQGfjs)
(3ChdgG (B:s
(3eHJhQ GdChd, hjHOC GdehLhO efg Hbhdg(B: (3hLhO GdefY hYOeg ajchf MGdg eY JeGe GdYdI cMGdg (B... (3adG jchf eG aQV YdI heQLMG(B...s
(3BNQgG (B:s
...(3hdcf ef fXQ ajg HYjf GdbHhd hGdQVG jLO ajgG ETGQGJ Edi ahGFO hJdhjMGJ Edi RhGFO NdJ YfgG GdcJH GdeJYGQaI hGdRHQ GdeJOGhdI(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds